Fragment optimization and elaboration strategies – the discovery of two lead series of PRMT5/MTA inhibitors from five fragment hits. Issue 12 (27th September 2022) - Smith, Christopher R.; Kulyk, Svitlana; Ahmad, Misbha Ud Din; Arkhipova, Valentina; Christensen, James G.; Gunn, Robin J.; Ivetac, Anthony; Ketcham, John M.; Kuehler, Jon; Lawson, J. David; Thomas, Nicole C.; Wang, Xiaolun; et al.
Abstract : Herein we describe our approach to prioritize five fragment hits with the objective of answering three questions: could the binding potency be improved? Were the series chemically tractable? Could additional co-crystal structures be solved? Abstract : Here we describe the early stages of a fragment-based lead discovery (FBLD) project for a recently elucidated synthetic lethal target, the PRMT5/MTA complex, for the treatment of MTAP -deleted cancers. Starting with five fragment/PRMT5/MTA X-ray co-crystal structures, we employed a two-phase fragment elaboration process encompassing optimization of fragment hits and subsequent fragment growth to increase potency, assess synthetic tractability, and enable structure-based drug design. Two lead series were identified, one of which led to the discovery of the clinical candidate MRTX1719.